Investigation of mechanical and friction properties of polytetrafluoroeethylene modified by nanopowder zirconium dioxide. - Свідерський, В.П.; Константинова, Т.Є.; Кириченко, Л.М.; Декалюк, Д.Ю. (Problems of Tribology, 2015)
Sviderskiy V.P., Кonstantinova Т.E., Kirichenko L.M., DekalyukD.U. Investigation of mechanical and friction properties of polytetrafluoroeethylene modified by nanopowder zirconium dioxide.The analysis of the properties of polytetrafluoroethylene and methods of his modification. Research of physicome-chanical and antifriction properties antifriction F4K20 modified by nanopowder zirconium dioxide has shown the expediency of application of the latest materials in friction units of machines and mechanisms.